2004
DOI: 10.1108/00251740410504412
|View full text |Cite
|
Sign up to set email alerts
|

Organizational citizenship behavior: a case study of culture, leadership and trust

Abstract: The aims of this study are to find out and to analys: (1) the influence of spiritual intelligence on organizational citizenship behavior; (2) the influence of leadership on organizational citizenship behavior; (3) the influence of organizationan culture on organizational citizenship behaviorThe population included all employees of Islamic Bank in Makassar City. There were 178 samples determined by using Slovin formula. The samples were selected in two stages: proportional and purposive sampling. The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(85 citation statements)
references
References 25 publications
5
69
1
4
Order By: Relevance
“…Carmeli and Josman (2006) investigated the relationship between emotional intelligence (BarYOn, 2000) and two characteristics of work outcomes including task performance and two types of organizational citizenship behaviors, altruism and compliance an reported positive relationships between emotional intelligence and employees' work outcomes. Appelbaum et al (2004) developed an action plan to move from current culture to preferred expressed culture beginning by rewarding team activity rather than individual activities; improving employee satisfaction even if the observed level were medium to high. Bienstock et al (2003) studied organizational citizenship behavior, with its framework of organizational rights and responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Carmeli and Josman (2006) investigated the relationship between emotional intelligence (BarYOn, 2000) and two characteristics of work outcomes including task performance and two types of organizational citizenship behaviors, altruism and compliance an reported positive relationships between emotional intelligence and employees' work outcomes. Appelbaum et al (2004) developed an action plan to move from current culture to preferred expressed culture beginning by rewarding team activity rather than individual activities; improving employee satisfaction even if the observed level were medium to high. Bienstock et al (2003) studied organizational citizenship behavior, with its framework of organizational rights and responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of the paper treated by management and got involved in organization programs. An employee, who feels respected and treated fairly, will not only trust the management, but the organization as well (Appelbaum, Bartolomucci, Beaumier, Boulanger, Corrigan, Doré, Girard, & Serroni 2006) Based on the explanation above, we can say that excellent communication and organizational culture in the end will enhance employees' trust and loyalty. Dani, Burns, Blackhouse and Kochhar (2006) propose that trust is generally.…”
Section: Model (Eskildsen and Nussler 2000)mentioning
confidence: 99%
“…Along these lines, business scholars have long observed that members of firms often have dual aspects that influence their behaviors: aspects germane to the organization and other aspects germane to themselves (Barnard, 1938, p. 88). In this sense, culture is a midwife of sorts to organizational behavior, that is, an element uniquely necessary to explain a firm's inimitable human side, such as organizational citizenship behaviors and effective leadership (Appelbaum et al, 2004).…”
Section: Firm Culture In Contextmentioning
confidence: 99%